Detection of Yersinia pestis in rodents and other small mammals in the northeast of Brazil during the period from 1966 to 1982 - Almeida, Alzira Maria Paiva de; Brasil, Darci Pascoal; Carvalho, Francisco Gomes de; Almeida, Célio Rodrigues de (Revista de Saúde Pública, 1987)
The analysis of the methods employed and the results obtained in the research into Yersinia pestis in 24.703 rodents and other small mammals from plague foci in the Northeast of Brazil during the period from 1966 to 1982, shows that the examinations should be carried out more guickly, to make prompter use of the data obtained in the activities of plague surveillance and control possible.